CuO nanoparticles’ effect on the photosynthetic performance in seed tissues of Inga laurina (Fabaceae) - Graciano, Daniela Espanguer; Pontes, Montcharles Silva; Araujo, Leandro Oliveira; Lima, Regiane Godoy; Grillo, Renato [UNESP]; Machulek, Amilcar; Santiago, Etenaldo Felipe; Oliveira, Samuel Leite; Caires, Anderson Rodrigues Lima (Springer Nature, 2024)
Copper oxide nanoparticles (CuONPs) have been produced on a large scale because they can be applied across various fields, especially in nano-enabled healthcare and agricultural products. However, the increasing use of CuONPs leads to their release and accumulation into the environment. The CuONPs uptaken by seeds and their implications on germination behavior have been reported, but little is known or understood about their impact on photosynthesis in seed tissues. To fill knowledge gaps, this study evaluated the effects of CuONP concentrations (0–300 mg L−1) on the photosynthetic activity of Inga laurina seeds. The microscopy data showed that CuONPs had an average size distribution of 57.5 ± 0.7 nm. Copper ion release and production of reactive oxygen species (ROS) by CuONPs were also evaluated by dialysis and spectroscopy experiments, respectively. CuONPs were not able to intrinsically generate ROS and released a low content of Cu2⁺ ions (4.5%, w/w). Time evolution of chlorophyll fluorescence imaging and laser-induced fluorescence spectroscopy were used to monitor the seeds subjected to nanoparticles during 168 h. The data demonstrate that CuONPs affected the steady-state maximum chlorophyll fluorescence (Fm′), the photochemical efficiency of photosystem II (Fv/Fm), and non-photochemical quenching (NPQ) of Inga laurina seeds over time. Besides, the NPQ significantly increased at the seed development stage, near the root protrusion stage, probably due to energy dissipation at this germination step. Additionally, the results indicated that CuONPs can change the oscillatory rhythms of energy dissipation of the seeds, disturbing the circadian clock. In conclusion, the results indicate that CuONPs can affect the photosynthetic behavior of I. laurina seeds. These findings open opportunities for using chlorophyll fluorescence as a non-destructive tool to evaluate nanoparticle impact on photosynthetic activity in seed tissues. Graphical abstract: (Figure presented.)
Keywords: Chlorophyll fluorescence; Copper oxide; Inga laurina; Nanoparticle; Photosynthetic activity; Seed